Authority and the sacred aspects of the Christianisation of the Roman world - Brown, Peter 1935- (Cambridge Univ. Press, 1995)
The Christianisation of the Roman world lies at the root of modern Europe, yet at the time it was a tentative and piecemeal process. Peter Brown's study examines the factors which proved decisive and the compromises which made the emergence of the Christian 'thought world' possible. He shows how contemporary narratives wavered between declarations of definitive victory and a sombre sense of the strength of the pre-Christian past, reflecting the hopes and fears of different generations faced with different social and political situations. He examines the social factors which muted the sharp intolerance which pervades the contemporary literary evidence, and he shows how Christian holy men were less representatives of a triumphant and intransigent faith than negotiators, at ground level, of a working compromise between the new faith and traditional ways of dealing with the supernatural world. His illuminating analysis of religious change as the art of the possible has a wide relevance for other periods and regions.
Keywords: Kirchengeschichte 30-600; Kerstening; Kirchengeschichte; Church history -- Early church, ca. 30-600; Geschichte; Christianisierung; Rom; Rome -- Religion; Römisches Reich; Aufsatzsammlung